POTENSI SUMBERDAYA DANAU DEPATI EMPAT BERBASISKAN ADO-ODTWA DI TAMAN NASIONAL KERINCI SEBLAT: Potential Resources of Lake Depati Empat based on ADO-ODTWA Assesment in Kerinci Seblat National Park - Albayudi Albayudi; Cory Wulan; Loki Susanti (Fakultas Kehutanan Universitas Jambi, 2021)
Kerinci Seblat National Park (TNKS) is a conservation area with an area of â€‹â€‹1,389,509,867 hectares. The form of utilization in the national park area that is considered to be able to provide sustainable benefits in increasing the income of local communities and preserving the area is maintained ecotourism. Depati Empat Lake is one of the tourist areas in the Kerinci Seblat National Park. Lake Depati Empat has the potential for diversity of flora and fauna around the lake, the potential of lake waters such as fish species and the potential of environmental services (landscapes) with aesthetic value which is very potential to be developed as an ecotourism area. Therefore this study aims to analyze the potential resources of Lake Depati Empat by using ADO-ODTWA analysis. The method of collecting data is done through field observations, questionnaire interviews and literature studies. The results showed that Lake Depati Empat was based on the ADO-ODTWA assessment results in the Lake Depati area. Four assessment components that received high potential value included tourist attraction, supporting facilities and infrastructure, carrying capacity of the area and the availability of clean water while accessibility and accommodation gained potential value, so that Lake Depati Empat gets very potential criteria to be developed as a natural tourism destination (ecotourism).Â